Study of Ethylene 1-Hexene Addition on Elongation, Tensile Strength and Cling Values of Stretch Wrap Plastics - Helmi Mustafa, Yoga Nawaki; Hanum, Farrah Fadhillah; Rahayu, Aster; Febriani, Annisa Vada (Indonesian Journal of Chemical Engineering, 2024)
Stretch wrap plastic is a very important packaging material on a variety of scales. It provides flexibility, strength, and transparency that make it indispensable for packaging goods efficiently. This research aims to investigate the effect of stretch wrap plastic thickness on its mechanical properties and analyze the impact of ethylene 1-hexene addition on these properties. The research was conducted using stretch wrap plastic samples made from linear low-density polyethylene (LLDPE) with varying thickness and percentage of ethylene 1-hexene addition. The test method involved elongation, tensile strength, and cling testing using a Universal Testing Machine (UTM). The results showed that the thickness of stretch wrap plastic affects its mechanical properties. The thicker the plastic, the higher the elongation and tensile strength values, while the stickiness tends to decrease.  The optimal thickness of stretch wrap plastic is 20 µm. The addition of ethylene 1-hexene also has a positive effect on the elongation and tensile strength properties, with the optimal percentage of addition at 55% with respect to components such as density and melt index